Self-nanoemulsifying drug delivery systems ameliorate the oral delivery of silymarin in rats with Roux-en-Y gastric bypass surgery - Chen CH (Dove Medical Press, 2015)
Chun-Han Chen,1,2 Cheng-Chih Chang,1 Tsung-Hsien Shih,2 Ibrahim A Aljuffali,3 Ta-Sen Yeh,4,5 Jia-You Fang6–8 1Division of General Surgery, Department of Surgery, Chang Gung Memorial Hospital, Chiayi, 2Graduate Institute of Clinical Medical Sciences, College of Medicine, Chang Gung University, Kweishan, Taoyuan, Taiwan; 3Department of Pharmaceutics, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 4Department of Surgery, Chang Gung Memorial Hospital, 5School of Medicine, College of Medicine, 6Pharmaceutics Laboratory, Graduate Institute of Natural Products, 7Chinese Herbal Medicine Research Team, Healthy Aging Research Center, Chang Gung University, 8Research Center for Industry of Human Ecology, Chang Gung University of Science and Technology, Kweishan, Taoyuan, Taiwan Abstract: Roux-en-Y gastric bypass (RYGB) is a popular surgery to reduce the body weight of obese patients. Although food intake is restricted by RYGB, drug absorption is also decreased. The purpose of this study was to develop novel self-nanoemulsifying drug delivery systems (SNEDDS) for enhancing the oral delivery of silymarin, which has poor water solubility. The SNEDDS were characterized by size, zeta potential, droplet number, and morphology. A technique of RYGB was performed in Sprague-Dawley rats. SNEDDS were administered at a silymarin dose of 600 mg/kg in normal and RYGB rats for comparison with silymarin aqueous suspension and polyethylene glycol (PEG) 400 solution. Plasma silibinin, the main active ingredient in silymarin, was chosen for estimating the pharmacokinetic parameters. SNEDDS diluted in simulated gastric fluid exhibited a droplet size of 190 nm with a spherical shape. The nanocarriers promoted silibinin availability via oral ingestion in RYGB rats by 2.5-fold and 1.5-fold compared to the suspension and PEG 400 solution, respectively. A significant double-peak concentration of silibinin was detected for RYGB rats receiving SNEDDS. Fluorescence imaging showed a deeper and broader penetration of Nile red, the fluorescence dye, into the gastrointestinal mucosa from SNEDDS than from PEG 400 solution. Histological examination showed that SNEDDS caused more minor inflammation at the gastrointestinal membrane as compared with that caused by PEG 400 solution, indicating a shielding of direct silymarin contact with the mucosa by the nanodroplets. SNEDDS generally showed low-level or negligible irritation in the gastrointestinal tract. Silymarin-loaded SNEDDS were successfully developed to improve the dissolution, permeability, and oral bioavailability of silymarin. To the best of our knowledge, this is the first investigation reporting the usefulness of SNEDDS for improving drug malabsorption elicited by gastric bypass surgery. Keywords: self-nanoemulsifying drug delivery system, Roux-en-Y gastric bypass, obesity, oral delivery, silymarin